有阶词表与汉藏语亲属关系研究 = A study of word rank list and Sino-Tibetan hypothesis - 吴晋琳 Tan, Yu Chen (2012)
历史比较法一直被认为是判定汉藏语亲属关系的最佳途径。然而陈保亚（1995）通过对汉傣语接触机制的追踪研究发现语言接触“无界有阶”的特点，提出“语音对应仅仅是确定同源关系的必要条件而不是充要条件”的看法。为此，其建立了有阶词表，利用绝对有阶分析法对语言的亲属关系做出判定，为同源关系的判定另辟新路。本文旨在将这一方法应用在汉藏语亲属关系之上。然而，陈氏的有阶词表在择词上缺乏明确的依据，使其操作力与稳定度遭到质疑。为此，本文引入两项实证研究——1） 何佩芩（2010）新有阶词表；2） Haspelmath et al. （2009） 的The Leipzig-Jakarta List of Basic Vocabulary，将理论推导和实际经验研究的结果相结合，对陈氏的有阶词表进行修改，制定了新有阶核心词表（分为前后阶各56词）。为找出最早时间层面的对应语素，陈保亚与汪锋（2006）为有阶核心词表确认了上古汉语中的对应词。然而汪维辉（2007）发现陈、汪在确定对应词的过程中对材料的选择和处理上大有问题。为此，本文在陈、汪研究的基础上参考了汪维辉之说法对上古汉语核心对应词进行确认，形成新的上古汉语核心词有阶词表。The Comparative Method is considered as an optimal approach to determine the relationship between languages. However, Chen (1995) found that language contact is unbounded but with stages. Therefore, he claimed that sound correspondence is only necessary but insufficient condition to establish cognate relation. He then created the word rank list and employed the relativistic rank analysis to determine the relationship between languages. This paper aims to apply Chen (1995)’s analysis method on examining the relationship between Chinese and Tibeto-Burman languages. The practicability and stability of Chen (1995)’s word rank list was questioned due to its lack of a clear standard on selecting words. To address the issue, this paper combines the results from two empirical researches, namely Ho (2010) and Haspelmath et al. (2010), and theoretical researches to construct a new fundamental word rank list. To identify the earliest corresponding morphemes, Chen & Wang (2006) ascertained the corresponding word of the fundamental word list in Archaic Chinese. However, Wang (2007) found that there were many flaws in the process of selecting and handling materials in Chen & Wang (2006). As such, this paper also refines the Archaic Chinese fundamental word list based on the two following findings.